La participación de los peregrinos en la fiesta de la Coronación de la Virgen de Chiquinquirá, Colombia: momentos y permanencias (2021)
This article analyzes the moments of pilgrims’ participation in the religious festival of the Coronation of the  Virgin of the Rosary of Chiquinquirá, in order to recognize the social ties, roles, bonds and permanence that are built over time. For this purpose, a research with a qualitative and ethnographic approach was carried out, which focused on observation, interviews and conversations with pilgrims during the fieldwork conducted between 2018 and 2019. The ethnographic work describes the actions carried out by the pilgrims to get involved in the festivity, delves into the devotees' points of view and the significance that the Virgin of Chiquinquirá has for them. It is important to point out that the role of the pilgrim highlights the idea that the festival pinpoints socially attributed traditional values and that it builds a source of unity and collective integration fundamental in the cultural development of the communities. In addition, it is understood that the festival of the Coronation —in its patronal character— has as its main attribute the tradition introduced by the pilgrims to visit the sanctuary of the Virgin of Chiquinquirá, imprinting a communitarian sense, of collective, meaningful and identity construction throughout the years.